"Measuring the Effectiveness of Academic Supervision in Achieving Quality Learning in Senior High Schools": "Measuring the Effectiveness of Academic Supervision in Achieving Quality Learning in Senior High Schools" - Amalia lia; gugun Gunadi (Jurnal Tunas Pendidikan, 2025)
Academic supervision plays a strategic role in improving the quality of education, particularly at the senior high school (SMA) level. This study aims to examine the extent to which academic supervision is effective in supporting the realization of quality learning. The research method employed is qualitative with a descriptive approach, involving literature review, interviews, and observations of supervision practices in schools. The findings indicate that academic supervision functions not only as a control mechanism but also as a means of professional development that enhances teachers’ pedagogical and professional competencies. The effectiveness of supervision is reflected in structured planning, active teacher involvement, and follow-up actions in the form of continuous reflection and improvement. However, several challenges remain, such as limited time, varying supervisory skills, and resistance from some teachers. Therefore, academic supervision conducted consistently, collaboratively, and based on teachers’ needs has proven to make a significant contribution to creating a more interactive, meaningful, and student-centered learning process.